2017
DOI: 10.1186/s40413-017-0166-z
|View full text |Cite
|
Sign up to set email alerts
|

Two case reports of desensitization in patients with hypersensitivity to iron

Abstract: Background: Iron deficiency anemia is a disease that can significantly compromise a patient's quality of life. Desensitization is a safe and effective treatment option for iron-deficient anemic patients who require intravenous iron despite their hypersensitivity to iron. This report describes a safe desensitization protocol for patients with iron hypersensitivity who require iron treatment for their clinical improvement. Case presentation: Two patients of 20 and 46-year-old diagnosed with secondary iron defici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 9 publications
2
16
0
Order By: Relevance
“…Notably, desensitization was effective for both oral iron and IV preparations. These results are in line with the sparse reports existing in the literature describing desensitization for iron products [2][3][4][5][6].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Notably, desensitization was effective for both oral iron and IV preparations. These results are in line with the sparse reports existing in the literature describing desensitization for iron products [2][3][4][5][6].…”
Section: Discussionsupporting
confidence: 91%
“…In particular, intravenous (IV) iron therapy is widely used when oral iron preparations are not tolerated or ineffective. Indeed, IV iron improves iron storages more rapidly [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Following full review, 15 articles were excluded, leaving 11 articles included in the final review: one guidance document on managing hypersensitivity reactions to IV iron , one consensus report on iron management in chronic kidney disease , three reviews of hypersensitivity reactions , two articles assessing incidence and comparative risks , and four articles describing case reports of signs, symptoms and managing reactions . Review of the references of these articles, as well as personal records of the panel, identified an additional eight articles: one review of hypersensitivity reactions ; two analyses of the rates of reaction with IV iron based on observational data ; four articles describing case reports of signs, symptoms and managing reactions ; and the European Medicines Agency (EMA)'s assessment report for iron‐containing IV medicinal products, a comprehensive review of available safety data on IV iron, including post‐marketing incident reports .…”
Section: Resultsmentioning
confidence: 99%
“…While infusion rates and the timing of escalation may differ in various low reactogenic protocols, all such protocols start the infusion at a very low rate such that 0·001–0·01% of the full dose is infused in the first 5–15 min . More recently, desensitization protocols for IV iron administration in individuals with a history of anaphylaxis to IV iron have been published . Both low reactogenic and desensitization protocols often include pretreatment with systemic corticosteroids and antihistamines.…”
Section: Discussionmentioning
confidence: 99%